Exploitation Feminism: Trashiness, Lo-Fidelity and Utopia in She-Devils on Wheels and Blood Orgy of the Leather Girls - Kristina Pia Hofer (Transatlantica)
From the mid-1960s onwards, American exploitation cinema has spawned a number of Girl Gang movies whose potential for challenging androcentric and heteronormative modes of representation have been hotly disputed by fans and academics alike. This article discusses this potential by sounding the trashy material textures of two outstanding Girl Gang films: She-Devils on Wheels (Herschell Gordon Lewis, 1968) and Blood Orgy of the Leather Girls (Michael Lucas, 1988). To date, excessive materialities in exploitation cinema have often been understood as traces of actual, historical bodies, objects, and practices. This paper suggests a different approach: by addressing how Lucas appropriates and reworks the outdated aesthetics, especially the untimely lo-fidelity sound, that distinguish Lewis’s earlier Girl Gang film, I will show how both films propel a utopian, fantastic, exaggerated “exploitation feminism,” instead of documenting historical feminist movements of their times. Taking the potential of trashy (sonic) textures seriously on their own terms, I will discuss the particular critical impulses such materially excessive exploitation feminisms can provide for a feminist reception of Girl Gang exploitation cinema today.